Фантасмагория, или Сказки третьего тысячелетия: повести / Александр Романов - Романов Александр Анатольевич (Луч, 2011)
Экземпляры: абонемент (20210202) / Инвентарный номер: 43264 / Цена: 230.08 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Р 69 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44